The Historiography of Sectarianism in Lebanon - Weiss, Max (History compass, 2009)
Lebanese history has been more or less defined by its engagement with the problem of sectarianism. Surprisingly rare have been the attempts to systematically trace this trajectory of historical engagement with the problem of sectarianism, though. This article argues that historians, legal scholars, and other writers have employed numerous conceptual and methodological approaches to examine, diagnose, and propose treatments for the problem of sectarianism, and that these approaches, moreover, have changed over time. Ranging from defenses of sectarianism as cultural specificity to condemnations of it as a foreign plot to divide and rule, the historiography of sectarianism in Lebanon has relied on such diverse fields as social science, constitutional law, political theory, and various kinds of historicism. Unfortunately, despite this empirical density, intellectual, legal, and historical discourses on sectarianism have failed to mitigate the material, political, and, most importantly, human costs incurred by the phenomenon of sectarianism in practice.